The Role of Working Memory, Short-Term Memory, Speed of Processing, Education, and Locality in Verb-Related Morphosyntactic Production: Evidence From Greek - Fyndanis, Valantis; Masoura, Elvira; Malefaki, Sonia; Chatziadamou, Efpraxia; Dosi, Ifigeneia; Caplan, David (Frontiers in psychology, 2022)
This study investigates the relationship between verb-related morphosyntactic production (VRMP) and locality (i.e., critical cue being adjacent to the target or not), verbal Working Memory (vWM), nonverbal/visuospatial WM (nvWM), verbal short-term memory (vSTM), nonverbal/visuospatial STM (nvSTM), speed of processing, and education. Eighty healthy middle-aged and older Greek-speaking participants were administered a sentence completion task tapping into production of subject–verb Agreement, Time Reference/Tense, and grammatical Aspect in local and nonlocal configurations, and cognitive tasks tapping into vSTM, nvSTM, vWM, nvWM, and speed of processing. Aspect elicited worse performance than Time Reference and Agreement, and Time Reference elicited worse performance than Agreement. There were main effects of vSTM, vWM, education, and locality: the greater the participants’ vSTM/vWM capacity, and the higher their educational level, the better their VRMP; nonlocal configurations elicited worse performance on VRMP than local configurations. Moreover, vWM affected Aspect and Time Reference/Tense more than Agreement, and education affected VRMP more in local than in nonlocal configurations. Lastly, locality affected Agreement and Aspect (with nonlocal configurations eliciting more agreement and aspect errors than local configurations) but not Time Reference. That vSTM/vWM (but not nvSTM/nvWM) were found to subserve VRMP suggests that VRMP is predominantly supported by domain-specific, not by domain-general, memory resources. The main effects of vWM and vSTM suggest that both the processing and storage components of WM are relevant to VRMP. That vWM (but not vSTM) interacts with production of Aspect, Time Reference, and Agreement suggests that Aspect and Time Reference are computationally more demanding than Agreement. These findings are consistent with earlier findings that, in individuals with aphasia, vWM interacts with production of Aspect, Time Reference, and Agreement. The differential effect of education on VRMP in local vs. nonlocal configurations could be accounted for by assuming that education is a proxy for an assumed procedural memory system that is sensitive to frequency patterns in language and better supports VRMP in more frequent than in less frequent configurations. In the same vein, the interaction between locality and the three morphosyntactic categories might reflect the statistical distribution of local vs. nonlocal Aspect, Agreement, and Time Reference/Tense in Greek.